Evidence-based guidelines for the pharmacological management of attention deficit hyperactivity disorder: Update on recommendations from the British Association for Psychopharmacology. (March 2014) - Bolea-Alamañac, Blanca; Nutt, David J; Adamou, Marios; Asherson, Phillip; Bazire, Stephen; Coghill, David; Heal, David; Müller, Ulrich; Nash, John; Santosh, Paramala; Sayal, Kapil; Sonuga-Barke, Edmund; et al.
Attention deficit hyperactivity disorder (ADHD) is a common condition with a high societal burden. The present guidelines summarise current literature, generating expert consensus recommendations for the treatment of ADHD in children and adults. These guidelines also provide a review of recent research in the fields of neuroimaging, neuropsychology and genetics of ADHD. Novel discoveries in these areas have informed physiological models for the disease. Since the publication of the previous British Association for Psychopharmacology guidelines in 2008, new drugs have been licensed and further compounds are being investigated. The publication of randomised controlled trials of psychological interventions has contributed to the range of treatment options for ADHD. As the disorder has been diagnosed more frequently there has been greater focus on comorbid conditions and how they impact treatment. Services have continued to develop for the treatment of ADHD in adults and care agreements have been introduced to facilitate access to treatment.